1 answer

(click or scroll down)

## To simplify the expression 3âˆš((3x^2y)^3), you need to apply the rules of exponentiation and radicals.

First, raise the quantity inside the parentheses to the power of 3:

(3x^2y)^3 = 27x^6y^3

Next, take the cube root of the result:

âˆ›(27x^6y^3) = âˆ›(3^3 * (x^2)^3 * (y^3)^1)

Now, simplify each term inside the cube root:

âˆ›(27x^6y^3) = âˆ›(27) * âˆ›(x^6) * âˆ›(y^3)

The cube root of 27 is 3, the cube root of x^6 is x^2, and the cube root of y^3 is y.

Therefore, the simplified expression becomes:

3 * x^2 * y = 3x^2y